2017
DOI: 10.1093/rheumatology/kex300
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the frequency of cardiovascular risk factors in patients with Takayasu’s arteritis

Abstract: CV risk factors are more common in patients with TAK, particularly hypertension. The FRS is higher in patients with TAK at the time of diagnosis. The cumulative incidence of CVE was also significantly higher during follow-up in TAK. Our results suggest that patients with TAK should undergo careful assessment of CV risk factors, and an aggressive risk modification approach is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 25 publications
2
30
1
2
Order By: Relevance
“…However, we also did not observe a significant association between the use of aspirin and risk of cardiovascular events. The effect of aspirin seems controversial, with another study reporting no significant effect of aspirin on the risk of cardiovascular events [4], consistent with our present study. Aspirin and statins are commonly used for cardioprotection; therefore, their effects are likely to be confounded by indication.…”
Section: Discussionsupporting
confidence: 88%
“…However, we also did not observe a significant association between the use of aspirin and risk of cardiovascular events. The effect of aspirin seems controversial, with another study reporting no significant effect of aspirin on the risk of cardiovascular events [4], consistent with our present study. Aspirin and statins are commonly used for cardioprotection; therefore, their effects are likely to be confounded by indication.…”
Section: Discussionsupporting
confidence: 88%
“…A recent paper highlighted increased incident cardiovascular events as well as higher Framingham Risk scores in a large cohort of patients with TA; higher risk (HR 4.36, 95% CI 1.25–15.13) for cardiovascular events was noted in TA when compared with the general population. This reinforces the needs to address cardiovascular risk factors in addition to hypertension in patients with TA . In this context, a recent study demonstrated beneficial effects of exercise in six patients with TA, with reductions in inflammatory cytokine TNF‐α and increase in levels of angiogenic factors in peripheral blood following a 12‐week exercise program .…”
Section: Comorbidities Associated With Uncontrolled Disease Activity mentioning
confidence: 55%
“…АГ традиционно относится к ФР сосудистых осложнений и определяется в 45-85% случаев АТ [2]. Данные представленной когорты полностью соответствуют результатам, полученным в других популяциях [2,5].…”
Section: Discussionunclassified
“…Высокий риск развития КВО среди пациентов АТ при оценке по алгоритму SCORE (Systematic Coronary Risk Evaluation) неоднократно отмечался в последние годы [5]. Однако наличие избыточной массы тела и инсулинорезистентности, а также неконтролируемая высокая активность заболевания ассоциировалась с еще более высоким риском развития МАСЕ, не учитываемым SCORE [7,8].…”
Section: Discussionunclassified